In Hot Arid Region... Tunnel technology for quality produce - Choudhary, B R; Saroj, P L (Indian Horticulture, 2019)
During May-June, temperature reaches up to 48Â°C which limit the production of cucurbits under open field conditions. Under such conditions, the advancement of crop is the only option to harvest quality produce. Therefore, low tunnel technology suitable for hot arid region has been standardized for different cucurbits. An advancement of 30-50 days has been observed in harvesting over their normal season of cultivation. Off-season cucurbits produced under tunnels fetch very high price in market. On an average, 2-3 fold benefit can be obtained under hot arid conditions.